Method for preparing high-purity synthetic quartz sand from white carbon black
Through the two-step heat treatment of pressurized, the problem of low densification of white carbon black is solved, and the preparation of high-purity and high-density quartz sand is realized, which is suitable for high-end industries such as semiconductors.
Patent Information
- Application Number
- CN202411435774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-15
AI Technical Summary
In the prior art, the density of white carbon black is low, which affects the application of quartz sand in quartz crucibles. In addition, the traditional one-step calcination method has the problem of rapid growth of grains and sealing bubbles.
The two-step heat treatment method is used to improve the density of white carbon black. Under the pressurized state, during the densification process of white carbon black nanoparticles, the spacing between particles is small, making it easy to form a sintered neck. The two-step heat treatment involves bubble migration and elimination at lower temperatures, and then particles grow at higher temperatures, filling pores and voids to meet the requirements of high density.
Through the two-step heat treatment of pressurized carbon black, the density degree of white carbon black is significantly improved, and high-density and high-purity quartz sand is prepared to meet the purity and density requirements of semiconductor grade.
Smart Images

Figure CN119390344A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz sand preparation, and in particular to a method for preparing high-purity synthetic quartz sand from white carbon black. Background Art
[0002] With the rapid development of the global semiconductor industry, the rapid iteration of chip technology, and the miniaturization of process technology have put forward higher requirements for chip manufacturing technology, especially in the manufacturing process of high-end integrated circuits such as logic and storage. These processes have reduced the tolerance of silicon wafer defects to an extremely low level, and the cleanliness and consistency requirements for semiconductor crucibles have also increased accordingly, especially the inner layer purity requirements for high-purity semiconductor synthetic quartz crucibles have reached a high standard of more than 6N. At the same time, as a disposable consumable, the demand for high-purity quartz sand for quartz crucibles has increased year by year.
[0003] At present, the synthesis of high-purity quartz sand is mainly divided into two directions, one is the purification of natural quartz sand, and the other is chemical synthesis of quartz sand. The purity of natural quartz sand in my country is low and it is difficult to purify, so synthetic high-purity quartz sand is more suitable for my country's development trend. Synthetic quartz sand can achieve extremely high purity through methods such as chemical liquid deposition, and the purity can reach 6N-7N level, that is, more than 99.99999%, far exceeding natural quartz sand. The synthesis process can strictly control the conditions to produce quartz sand with high consistency and reduce the impurities and variability in natural ores. The preparation of high-purity synthetic quartz sand with white carbon black as a by-product of silane production can reduce dependence on traditional natural quartz sand resources and reduce the impact on environmental pollution. It not only solves the problem of waste disposal, but also provides a low-cost silicon source, making white carbon black an ideal raw material for the preparation of synthetic quartz stone. The use of silane by-products to prepare quartz sand is in line with the model of circular economy and green development, which helps to reduce the environmental impact of waste and provide a sustainable way of resource utilization. By converting industrial by-products into high-purity synthetic quartz sand, the economic added value of industrial by-product white carbon black is effectively improved, and it has high market demand and price in the semiconductor, photovoltaic and optical fiber fields.
[0004] At present, the method of densifying silica mainly adopts one-step calcination at normal pressure to heat treat it. This method is not conducive to the formation of sintering necks between particles because the nanoparticles are relatively loose and the distance between particles is far. At the same time, the one-step densification temperature is high, the grains grow rapidly, and the bubbles and pores inside the particles are quickly closed. Therefore, the degree of densification of silica is low, which affects the application of quartz sand in quartz crucibles.
[0005] The advantage of the pressurized two-step heat treatment used in the present invention to improve the density of white carbon is that the distance between the white carbon nanoparticles is small during the densification process under the pressurized state, and the pressure will increase the formation of sintering necks between the particles, which can easily form sintering necks. As the sintering necks grow, fusion occurs between the particles, promoting the regrowth of the particles. At the same time, the two-step heat treatment of the present invention still keeps the grains in a small state at a relatively low temperature, making it easy for the bubbles inside the particles to migrate and be expelled from the body. At a higher temperature, the particles grow and fill the pores inside the particles and the gaps between the particles, meeting the high densification requirements. Therefore, the development of a two-step heat treatment is beneficial to improving the densification degree of white carbon and meeting the product standards of high-quality quartz sand. Summary of the invention
[0006] The present invention provides a method for preparing high-purity synthetic quartz sand from white carbon black. The method of the present invention can successfully prepare high-density high-purity quartz sand by sequentially performing acid washing and purification, dehydroxylation, densification and other operations on the existing silane byproduct white carbon black.
[0007] [1] A method for preparing high-purity synthetic quartz sand from white carbon black, comprising the steps of:
[0008] S1, soaking white carbon black in a mixed acid solution of hydrofluoric acid and hydrochloric acid, taking out the solid, washing it, and drying it to obtain high-purity SiO2 powder;
[0009] S2, treating the high-purity SiO2 powder at high temperature to remove residual moisture and hydroxyl groups therein;
[0010] S3, crushing the product treated in step S2 into powder and pressing it into blocks;
[0011] S4, the block obtained in step S3 is subjected to densification heat treatment by a two-step calcination method, firstly heated to a lower temperature t1 (bubble migration temperature) for a short time, then heated to a higher temperature t2 (densification temperature) for a longer time, and cooled to obtain a high-density quartz block; t1 is selected from 1100 to 1200° C., and the t1 insulation time is 1 to 2 hours, which is conducive to sufficient discharge of bubbles; t2 is selected from 1300 to 1500° C., and the t2 insulation time is 2 to 10 hours (for example, 4 hours, 6 hours, 8 hours, etc.);
[0012] S5, crushing the high-density quartz block to obtain high-density high-purity quartz sand.
[0013] In step S1, in the mixed acid solution, the molar ratio of hydrofluoric acid to hydrochloric acid may be 1:1 to 5, for example, 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0014] In step S1, the mass ratio of the white carbon black to the mixed acid solution may be 1:1-3, such as 1:1, 1:2, 1:3, etc.
[0015] In step S1, the soaking time may be 10 to 20 hours.
[0016] In step S1, the cleaning may specifically include: washing with deionized water and ethanol for several times, and then centrifuging, and the obtained solid is used for subsequent drying to obtain high-purity SiO2 powder. Furthermore, the centrifugal speed is preferably not less than 6000 rpm.
[0017] In step S1, the drying may be vacuum drying. Furthermore, the vacuum drying temperature may be 100 to 105° C., and the vacuum drying time may be 1 to 24 hours.
[0018] In step S2, the heating rate of the high temperature treatment can be 5-10°C min -1 .
[0019] In step S2, the temperature of the high temperature treatment may be 800-1000°C.
[0020] In step S2, the high temperature treatment time may be 6 to 10 hours.
[0021] In some preferred embodiments, in step S2, the atmosphere of the high temperature treatment is a negative pressure inert environment of -0.1 MPa or lower. The inert environment refers to an atmosphere that does not participate in the reaction, such as nitrogen and / or a rare gas (such as argon, etc.). Negative pressure can be achieved by vacuuming after inert gas washing. The inert gas refers to a gas that does not participate in the reaction, such as nitrogen and / or a rare gas (such as argon, etc.).
[0022] In step S2, the high-purity SiO2 powder can be placed in a corundum crucible for high-temperature treatment.
[0023] In some embodiments, in step S3, the area of the pressing pressure is 0.785 cm 2 .
[0024] In step S3, the pressing pressure may be 100-400 MPa, preferably 300-400 MPa, which is beneficial to improving the density of high-purity quartz sand.
[0025] In some preferred embodiments, in step S4, the block obtained in step S3 is subjected to densification heat treatment by a two-step calcination method in a negative pressure inert environment of -0.1 MPa or lower. The inert environment refers to an atmosphere that does not participate in the reaction, such as an atmosphere of nitrogen and / or a rare gas (such as argon, etc.). Negative pressure can be achieved by vacuuming after inert gas washing. The inert gas refers to a gas that does not participate in the reaction, such as a gas such as nitrogen and / or a rare gas (such as argon, etc.).
[0026] Compared with the traditional one-step sintering process, the two-step vacuum sintering process of the present invention, which is "low temperature first and high temperature later", is more conducive to the densification of nano-scale SiO2 particles. Under applied pressure (e.g., 400MPa), the relatively low temperature insulation at t1 can effectively convert residual hydroxyl groups and chloride ions into bubbles, which migrate along the particle interface and internal pores to the pressureless environment and are discharged to the outside of the block; at t2, the grains begin to grow under the higher temperature and internal pressure, and sintering necks are formed between the particles under the high interface energy and diffusion. As the sintering necks grow, the particles are promoted to fuse and grow again, and the internal pores of the particles and the gaps at the interface between the particles are gradually filled, thereby realizing the synthesis of high-density quartz sand particles from nano-scale SiO2 particles.
[0027] In step S4, the heating rate to the lower temperature t1 can be 2-5°C min -1 , for example 3℃min -1 wait.
[0028] In step S4, the heating rate to the higher temperature t2 may be 2-5°C min -1 , preferably 2~3℃min -1 , which is beneficial to improve the density of high-purity quartz sand.
[0029] In step S4, t2 is preferably from 1400 to 1500° C., which is beneficial to improving the density of high-purity quartz sand.
[0030] In step S4, the insulation time t2 may be 6 to 10 hours.
[0031] In step S4, the cooling may be performed in stages. Further, the cooling rate in the first stage may be 1-10°C min -1 , for example 5℃min -1 The end point of the first stage cooling can be 300℃.
[0032] Figure 1 An exemplary densification heat treatment temperature rise and fall curve in a method for preparing high-purity synthetic quartz sand from white carbon black of the present invention is shown.
[0033] In step S5, the particle size of the high-purity quartz sand can be 50-310 μm, and can be further classified into 50-60 μm, 100-110 μm, 150-160 μm, 200-210 μm, 250-260 μm, and 300-310 μm.
[0034] In step S5, the tap density of the high-purity quartz sand is greater than 0.8 g cm -3 , further greater than 1.2 g cm -3 , and further greater than 1.4 g cm -3 .
[0035] In step S5, the purity of SiO2 in the high-purity quartz sand is greater than 4N8.
[0036] [2] Application of the method described in [1] in synthesizing high-purity quartz sand.
[0037] The present invention uses a mixed acid of hydrofluoric acid and hydrochloric acid to acid-wash and purify white carbon black to remove metal impurities; separates, washes and dries the obtained precipitation product to obtain high-purity SiO2 powder; performs dehydroxylation treatment by high-temperature heating under vacuum conditions; crushes and pressurizes the dehydroxylated product to form a block; performs densification heat treatment on it by a two-step calcination method to obtain a high-density quartz block; and performs crushing and screening treatment to prepare high-density high-purity quartz sand.
[0038] The method of the present invention can effectively utilize by-products in the silane production process, reduce environmental pollution and resource waste; through high-temperature calcination and acid washing purification, the purity of quartz sand is significantly improved to reach semiconductor-grade standards; the method is simple to operate, low in cost, and easy to industrialize.
[0039] The present invention solves the problem of recycling the existing silane byproduct white carbon black, improves the utilization efficiency of silicon resources, and simultaneously produces high-density and high-purity quartz sand with higher economic benefits, which is suitable for related semiconductor, optoelectronic, photovoltaic and other industries.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The present invention adopts a two-step sintering method to sinter silica into high-density quartz sand. Silica mainly includes amorphous SiO2 particles. The particle size of amorphous SiO2 particles is 80-100nm, which cannot meet the actual application scenarios of quartz sand. Therefore, it is necessary to increase the particle size and density of SiO2 particles. The present invention adopts a two-step sintering technology, which optimizes the microstructure of the material by controlling the sintering process, thereby improving the density of the material. The two-step sintering method can effectively control grain growth. By pre-sintering at a lower temperature t1 for a short time and then sintering at a higher temperature t2 for a long time, the grains can be refined to obtain a more uniform and fine grain structure. This method helps to increase the density of the material without significantly increasing the grain size, which is very important for improving the mechanical strength and hardness of the material. Due to grain refinement, the two-step sintering method can generally improve the fracture toughness, hardness and wear resistance of the material. By controlling the sintering temperature and time, abnormal grain growth can be reduced, which is crucial to maintaining the uniformity and reliability of the material. Compared with the traditional one-step high-temperature sintering method, the two-step sintering method can achieve high density at a lower temperature, thus saving energy and cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1The present invention provides an exemplary densification heat treatment temperature rise and fall curve diagram in a method for preparing high-purity synthetic quartz sand from white carbon black.
[0043] Figure 2 This is the X-ray diffraction (XRD) pattern of the powdered SiO2 particles in step 3 of Example 1.
[0044] Figure 3 This is the result of thermogravimetric analysis (TG-DTG) of powdered SiO2 particles in step 3 of Example 1.
[0045] Figure 4 This is a graph showing the thermal expansion test results of powdered SiO2 particles in step 3 of Example 1.
[0046] Figure 5 Metallographic photographs of high-density quartz blocks after heat treatment in step 4 of Example 1(a), Example 4(b), Example 6(c), Example 9(d) and Example 10(e). Figure 6 This is a scanning electron microscope photograph of the high-purity quartz sand of Example 4.
[0047] Figure 7 This is a scanning electron microscope photograph of the high-purity quartz sand of Example 9.
[0048] Figure 8 This is a comparison chart of the nitrogen adsorption BET specific surface areas of the powdered SiO2 particles (Sample 1) in step 3 of Example 4, the high-purity quartz sand (Sample 2) in step 5, and the powdered SiO2 particles (Sample 3) in step 3 of Example 6, and the high-purity quartz sand (Sample 4) in step 5.
[0049] Fig. 9 These are the nitrogen adsorption curves of the powdered SiO2 particles in step 3 of Example 4 (a), the high-purity quartz sand in step 5 (b), and the powdered SiO2 particles in step 3 of Example 6 (c), and the high-purity quartz sand in step 5 (d).
[0050] Fig.10 The pore size distribution diagrams are of the powdered SiO2 particles in step 3 of Example 4 (a), the high-purity quartz sand in step 5 (b), and of the powdered SiO2 particles in step 3 of Example 6 (c), and the high-purity quartz sand in step 5 (d).
[0051] Fig.11 The figure is a comparison chart of the tap density of high-purity quartz sand obtained under different pressures in Examples 1 to 4.
[0052] Fig.12 This is a comparison chart of the tap density of high-purity quartz sand obtained at different heating rates in Examples 4 to 6.
[0053] Fig.13 This is a comparison chart of the tap density of high-purity quartz sand obtained at different reaction times in Examples 6 to 9.
[0054] Fig.14 This is a real photo of the high-purity quartz sand in Example 9.
[0055] Fig.15 The actual photos and metallographic photos of the one-step sintering in Comparative Example 1, where: (a) the one-step sintering was performed at 800℃ for 10h, 900℃ for 10h, and 1000℃ for 10h; (b) the sample was subjected to a pressure of 100MPa for 2℃min -1 The heating rate was increased to 1400℃; (c) the sample was subjected to a pressure of 400MPa for 2℃min -1 The heating rate was increased to 1400℃; (d) the sample was subjected to a pressure of 100MPa for 2℃min -1 The heating rate was increased to 1500°C; (e) the sample was subjected to a pressure of 400 MPa for 2°C min -1 The heating rate was increased to 1500°C. DETAILED DESCRIPTION
[0056] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0057] Example 1
[0058] Step 1: Prepare 10 mL of a mixed solution of hydrofluoric acid and hydrochloric acid in a molar ratio of 1:1; weigh 10 g of white carbon black powder using an electronic balance and add it to the mixed acid solution and soak for 20 hours. Remove the upper layer of liquid, take out the lower layer of white precipitate and wash it repeatedly with deionized water and ethanol for several times, and heat it at 6000 r min. -1 After centrifugation at a high speed, a white powder was obtained, and high-purity SiO2 powder was obtained after vacuum drying at 100°C for 24 hours.
[0059] Step 2: Move the high-purity SiO2 powder into a corundum crucible and place it in a tube furnace. Purge it with nitrogen gas with a purity of ≥99.999% and evacuate it to a negative pressure of -0.1MPa. Repeat the purge and vacuum three times and set the temperature to 10℃min. -1 The heating rate was increased to 800 °C and kept for 10 h before cooling to room temperature to remove the residual moisture and hydroxyl groups in the powder.
[0060] Step 3: Crush the block obtained after removing the hydroxyl group in step 2 into powdered SiO2 particles, transfer the powdered SiO2 particles into a room temperature tablet pressing mold with a diameter of 10 mm, and apply a pressure of 100 MPa to press them into cylindrical blocks.
[0061] Step 4: The compacted cylindrical block is subjected to densification heat treatment by a two-step calcination method. The heat treatment atmosphere is achieved by the following operations: purging with nitrogen with a purity of ≥99.999% to a negative pressure of -0.1MPa, and purging and vacuuming are repeated three times. The heat treatment program is set as follows: first, 5℃ min -1 The heating rate is 5℃min to t1 temperature 1200℃, and then the temperature is kept at t2 for 2h. -1 The temperature was heated to 1400℃ at a rate of 100℃ and kept at that temperature for 2h. After the reaction was completed, the temperature was increased to 5℃ min -1 The cooling rate is reduced to 300°C and then cooled to room temperature to obtain a high-density quartz block.
[0062] Step 5: The high-density quartz block is crushed, ground, screened and graded to obtain high-density high-purity quartz sand of the required particle size, with SiO2 purity greater than 4N8.
[0063] Figure 2 This is the XRD spectrum of the powdered SiO2 particles in step 3 of Example 1. The test results show that the diffraction peak of the synthesized SiO2 powder is located at 22°, which is consistent with the standard amorphous SiO2 (JCPDS29-0085) card, proving that the obtained product is amorphous SiO2 powder without the presence of other impurity phases.
[0064] In order to study the physical and chemical changes of nano-scale SiO2 powder during heating, the powder SiO2 particles in step 3 of Example 1 were subjected to TG-DTG test analysis, and the test temperature range was 0-1500°C. The test results are shown in Figure 2. Figure 3 As shown, the mass loss is 4.5% at about 160°C. The DTG curve results show that the mass loss rate is the largest at 97.15°C, proving that the mass loss in this temperature range is mainly due to free water and coordinated water in the SiO2 structure. At a test temperature of about 800°C, the mass loss of the tested sample is 4.5%. The DTG curve results show that the mass loss rate is the largest at 428.33°C, proving that the mass loss in this temperature range is mainly due to the hydroxyl groups formed during the synthesis of SiO2. In the temperature range of 800-1500°C, the TG curve remains basically stable, proving that the hydroxyl groups have all been removed at 800°C.
[0065] In order to select the best test temperature for the two-step method, a thermal expansion test was performed on the powdered SiO2 particles in step 3 to study their volume change during the heating process. Figure 4As shown in the figure, when the temperature rises to 150℃, the volume of the test sample begins to shrink until 400℃. This is mainly due to the loss of free water and coordinated water in the SiO2 structure, and the internal structure of SiO2 begins to shrink, with a volume reduction of 0.9%. When the temperature rises from 400℃ to 1000℃, the volume shrinkage of this part is mainly due to the gradual loss of hydroxyl groups in the sample, and the volume further shrinks by 4.0%. When the temperature rises from 1000℃ to 1200℃, the volume shrinkage of this part is mainly attributed to the bubbles formed inside the sample sliding at the grain interface, and small bubbles mainly merge into large bubbles. Under vacuum negative pressure conditions, large bubbles gradually migrate to the surface of the sample and are gradually expelled from the body, with a volume shrinkage of 5.3%. As the temperature further rises to 1500℃, the sample volume further shrinks to form a dense structure. The thermal expansion curve can determine that the bubble migration temperature t1 in the sample is mainly concentrated in 1000-1200℃, and the densification t2 temperature is above 1400℃.
[0066] Embodiments 2 to 4
[0067] The only difference from Example 1 is that the pressing pressure in step 3 is changed to 200MPa (Example 2), 300MPa (Example 3) and 400MPa (Example 4) respectively, and the rest are the same, and high-density high-purity quartz sand with SiO2 purity greater than 4N8 is obtained.
[0068] Embodiment 5-6
[0069] The only difference from Example 4 is that the heating rate to t2 temperature 1400°C in step 4 is changed to 3°C min -1 (Example 5) and 2°C min -1 (Example 6), the rest are the same, and high-density high-purity quartz sand with SiO2 purity greater than 4N8 is obtained.
[0070] Embodiments 7 to 9
[0071] The only difference from Example 6 is that the insulation time of the temperature t2 at 1400°C in step 5 is changed to 4h (Example 7), 6h (Example 8), and 10h (Example 9) respectively, and the rest are the same, and high-density high-purity quartz sand with SiO2 purity greater than 4N8 is obtained.
[0072] Example 10
[0073] The only difference from Example 9 is that the temperature t2 in step 5 is changed to 1500°C, and the rest are the same, and high-density high-purity quartz sand with SiO2 purity greater than 4N8 is obtained.
[0074] like Figure 5As shown in (a), when the pressure applied to the sample in Example 1 is 100 MPa, the sample has a large number of bubbles inside after heat treatment, and the structure between the particles is relatively loose. Figure 5 (b) When the sample pressure was applied to 400 MPa, under the same heat treatment conditions, the bubble content in the obtained sample was significantly reduced, and the microstructure between the particles was relatively dense. -1 Reduce to 2℃min -1 (Example 6, Figure 5 (c)), the reaction time was extended from 2 h to 10 h (Example 9, Figure 5 (d)), the bubble content in the sample gradually disappeared, the particles were stacked more tightly, and the particle size was 100-200 μm. As the reaction temperature increased to 1500°C (Example 10, Figure 5 (e)), there are no obvious bubbles inside the sample, and the particles are stacked very tightly.
[0075] Example 4 Figure 6 ) and Example 9 ( Figure 7 ) show that with the decrease of heating rate and the extension of reaction time, the pores on the sample surface gradually close to form a dense SiO2 bulk structure.
[0076] BET test results ( Figures 8 to 10 ) showed that with the increase of pressure and reaction time, the specific surface area of the sample gradually decreased, proving that the pores inside the particles gradually closed, indicating that increasing pressure and reaction time can promote the growth of SiO2 particles and promote the densification of SiO2 particles.
[0077] Further analysis of the tap density distribution of calcined quartz sand particles, Figures 11 to 13 It shows that with the increase of pressure, the tap density of quartz sand particles increases significantly. At the same time, with the decrease of heating rate and the extension of reaction time, the tap density of quartz sand also increases gradually. The tap density of Example 9 can reach 1.41 g cm -3 , has reached the density requirements of commercial quartz sand ( Fig.14 ). The above results show that the increase of external pressure and the decrease of heating rate can effectively increase the activation energy of SiO2 particle interface, enhance the driving force of atomic diffusion at the interface, and promote the formation of sintering neck. At the same time, as the particles grow, the pores inside the particles will gradually fill and close, and the bubbles at the particle interface will gradually migrate and be removed, thereby improving the density of SiO2 particles.
[0078] Comparative Example 1
[0079] The powdered SiO2 particles obtained in step 3 were subjected to densification heat treatment by a one-step method. First, the powdered SiO2 particles were heated at 10°C min-1 without pressure. -1 The heating rate is 800℃, 900℃ and 1000℃ respectively. Fig.15 As shown in (a), the sample after heat treatment is still in powder state, and the powder SiO2 particles cannot be densified. The samples were pressurized to 100MPa and 400MPa respectively at 2℃min -1 Heating rate to 1400℃ and 1500℃( Fig.15 (be)), a large number of bubbles and pores can be observed on the surface and inside of the sample through metallographic photos. This is mainly due to the one-step calcination. Under low temperature conditions, the temperature cannot reach the nano-scale particle densification temperature; under high temperature conditions, as the temperature rises, the grains grow, and the bubbles inside the sample cannot migrate out of the sample. A large number of bubbles are fixed inside the particles, thereby reducing the density of the quartz sand.
[0080] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing high-purity synthetic quartz sand from white carbon black, characterized in that: Includes steps: S1, soaking white carbon black in a mixed acid solution of hydrofluoric acid and hydrochloric acid, taking out the solid, washing it, and drying it to obtain high-purity SiO2 powder; S2, treating the high-purity SiO2 powder at high temperature to remove residual moisture and hydroxyl groups therein; S3, crushing the product treated in step S2 into powder and pressing it into blocks; S4, the block obtained in step S3 is subjected to a densification heat treatment by a two-step calcination method, firstly heated to a lower temperature t1 and kept at the temperature for a shorter time, then heated to a higher temperature t2 and kept at the temperature for a longer time, and then cooled to obtain a high-density quartz block; t1 is selected from 1000 to 1200°C, and the t1 holding time is 1 to 2 hours; t2 is selected from 1300 to 1500°C, and the t2 holding time is 2 to 10 hours; S5, crushing the high-density quartz block to obtain high-density high-purity quartz sand.
2. The method according to claim 1, characterized in that In step S1: In the mixed acid solution, the molar ratio of hydrofluoric acid to hydrochloric acid is 1:1-5; The mass ratio of the white carbon black to the mixed acid solution is 1:1-3; The soaking time is 10 to 20 hours; The cleaning specifically includes: using deionized water and ethanol to wash repeatedly for several times, and then centrifuging, and the obtained solid is used for subsequent drying to obtain high-purity SiO2 powder; the rotation speed of the centrifuge is not less than 6000rpm; The drying is vacuum drying, the vacuum drying temperature is 100-105° C., and the vacuum drying time is 1-24 hours.
3. The method according to claim 1, characterized in that In step S2: The heating rate of the high temperature treatment is 5-10°C min -1 ; The temperature of the high temperature treatment is 800-1000°C; The high temperature treatment time is 6 to 10 hours; The atmosphere environment of the high temperature treatment is a negative pressure inert environment of -0.1 MPa or lower; The high-purity SiO2 powder is placed in a corundum crucible for high-temperature treatment.
4. The method according to claim 1, characterized in that In step S3, the pressing pressure is 100-400 MPa, preferably 300-400 MPa.
5. The method according to claim 1, characterized in that: In step S4, the block obtained in step S3 is subjected to densification heat treatment by a two-step calcination method in a negative pressure inert environment of -0.1 MPa or lower.
6. The method according to claim 1 or 5, characterized in that: In step S4: The heating rate to the lower temperature t1 is 2~5℃min -1 ; The heating rate to the higher temperature t2 is 2~5℃min -1 , preferably 2~3℃min -1 ; t2 is selected from 1400 to 1500°C; t2 insulation time is 6 to 10 hours; The cooling is carried out in stages, wherein the cooling rate in the first stage is 1-10°C min -1 , the end point of the first stage cooling is 300℃.
7. The method according to claim 1, characterized in that In step S5: The particle size of the high-purity quartz sand is 50-310 μm, which is further classified into 50-60 μm, 100-110 μm, 150-160 μm, 200-210 μm, 250-260 μm, and 300-310 μm; The tap density of the high-purity quartz sand is greater than 1.2 g cm -3 , further greater than 1.4 g cm -3 ; The purity of SiO2 in the high-purity quartz sand is greater than 4N8.
8. Use of the method according to any one of claims 1 to 7 in synthesizing high-purity quartz sand.
Citation Information
Patent Citations
Method for preparing high-purity metallurgical-grade silicon
CN102066250A
High-purity quartz sand purification method and special rotating device
CN103754889A
Preparation method of quartz lead
CN109160724A
Preparation method of quartziferous ceramic membrane support
CN113336567A
Method for producing white carbon black and preparing synthetic quartz block and high-purity quartz sand by taking fluosilicic acid solution as raw material
CN116692882A